Scientific language and its implication on science learning among schools students which undergo english medium of instruction - Nordin, Aziz; Husin, Hassan; Jonid, Muslim (Universiti Teknologi Malaysia, 2004)

(untitled)
The present research is a preliminary attempt to investigate some current issues on teaching science and mathematics in English. Three issues have been highlighted. These are i) Students perception on learning science and mathematics in English language. ii) Students ability to understand basic scientific terms used in science teaching. iii) Teacher trainees perception on teaching and learning science and mathematics in English language. Studies were conducted in several schools in Johor and Universiti Teknologi Malaysia to gather information regarding students perception and understanding of basic scientific terms as well as teacher trainees ability to teach science and mathematics in English.Questionnaires were used in this study. The results of the study showed that students in schools are actually encountered language problems as well as contents problems in learning science and mathematics and to overcome these problems they need help and guidance from the teachers. It is also found out that similar problems were faced by the teacher trainees regarding the use of English language in everyday life and in the classroom. The majority of teacher trainees have poor command in English and lack of confident in handling teaching activities in the classroom. Therefore, proper English language training programs should be implemented to the students and teacher trainees before they could learn and teach science and mathematics effectively.